Effects of Sport Stacking on Neuropsychological, Neurobiological, and Brain Function Performances in Patients With Mild Alzheimer's Disease and Mild Cognitive Impairment: A Randomized Controlled Trial - Yang, Ziying; Zhang, Wenbo; Liu, Dunxiu; Zhang, Shan-shan; Tang, Yong; Song, Jiaqi; Long, Jinfeng; Yang, Jun; Jiang, Hong; Li, Yaling; Liu, Xintong; Lü, Yang; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: To investigate the effects of sport stacking on the overall cognition and brain function in patients with mild Alzheimer’s disease (AD) and mild cognitive impairment (MCI). Methods: A single-blind randomized controlled design was performed using sport stacking for 30 minutes, 5 days/week for 12 weeks. Forty-eight subjects with mild AD or MCI were randomly divided into the sport stacking group (T-mAD=12, T-MCI=12) and the active control group (C-mAD=11, C-MCI=13). Auditory Verbal Learning Test (AVLT), Alzheimer’s Disease Cooperative Study–Activities of Daily Living scale (ADCS-ADL), Geriatric Depression Scale (GDS-30), and Pittsburgh Sleep Quality Index (PSQI) were performed, the level of amyloid β-protein-40 (Aβ-40), Aβ-42, brain-derived neurotrophic factor (BDNF), insulin-like growth factor-1(IGF-1), tumor necrosis factor-alpha (TNF-α), Interleukin-6 (IL-6), and soluble trigger receptor expressed on myeloid cells 2 (sTREM2) in plasma were tested, and brain functional connectivity in resting state and activation under finger movement task were analyzed by functional near-infrared spectroscopy (fNIRS). Results: 39 patients completed the trial. After 4 weeks, we found a significant increase in AVLT score in T-MCI (6.36±5.08 VS -1.11±4.23, p=0.004), and T-mAD group (4.60±4.77 VS -0.11±2.89, p=0.039). After 12 weeks, there was a significantly improved in AVLT (9.64±4.90 VS -0.33±6.10, p=0.002) and ADCS-ADL (3.36±3.59 VS -1.89±2.71, p=0.003) in T-MCI. There was a significant improvement in AVLT (5.30±5.42 VS 0.44±2.40) in T-mAD (p<0.05). Plasma levels of BDNF were upregulated in both T-MCI and T-mAD, and IGF-1 increased in T-MCI (P< 0.05) compared to the control groups. The functional connectivity in MCI patients between DLPFC.R and SCA.R, SMA.L, and SCA.R was decreased. In contrast, in mAD patients, the brain regional function connection was increased between DLPFC.R and Broca’s.L. The activation of channel 36 located in the left primary somatosensory cortex was significantly increased after 12-week training, which was correlated with the improved AVLT and the increase of BDNF. Conclusion: Our findings suggested that sport stacking is effective for patients with MCI and mild AD, possibly through increasing the expression of neuroprotective growth factors and enhancing neural plasticity to improve neurocognitive performance.